Beef cattle management practices [ - Albin, Robert C.; Davis, G. W.; Grant, Ron , 1927-; Lansdell, Jeff (CEV Multimedia, 2009)
Teaches that sound management and handling of beef cattle is essential to profitable beef production. The topics discussed include the basics of cattle handling including restraint, ingestation technique, dehorning, growth stimulant implants, and other matters, surgical and bloodless castration, external and internal parasites, artificial insemination and palpation. Generally, steers are preferred over bulls. Quizzes and a comprehensive exam and answers included at the end